Patterns of Social Interaction in Housing - Fadhilah, Alma Husna; Wiyanarti, Erlina; Logayah, Dina Siti (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2024)
Social interaction in the Housing Community has an important role in shaping relationships between individuals that can affect the quality of life in the Housing Community. This study aims to analyze the pattern of social interaction in the community in Bumi Parahyangan Kencana Housing, Bandung Regency. This research uses a qualitative approach to the case study method whose data collection was done by in-depth interviews, observation, and documentation. The results showed the pattern of social interaction of residents of Bumi Parahyangan Kencana Housing has different diversity in each type of house design. This is due to the adaptation of residents of Bumi Parahyangan Kencana Housing in conducting social interactions. It is concluded that the pattern of community interaction in Bumi Parahyangan Kencana Housing is in the form of associative social interaction patterns, but conflicts cannot be avoided by residents in every type of house design.